Experts consensus on management of tooth luxation and avulsion - Ruijie Huang; Chenchen Zhou; Ling Zhan; Yuan Liu; Xian Liu; Qin Du; Jun Wang; Wei Zhao; Guangtai Song; Li-an Wu; Beizhan Jiang; Yanhong Li; et al. (Nature Publishing Group, 2024)
Abstract Traumatic dental injuries (TDIs) of teeth occur frequently in children and adolescents. TDIs that impact the periodontal tissues and alveolar tissue can be classified into concussion, subluxation, extrusive luxation, intrusive luxation, lateral luxation, and avulsion. In these TDIs, management of injured soft tissue, mainly periodontal ligament, and dental pulp, is crucial in maintaining the function and longevity of the injured teeth. Factors that need to be considered for management in laxation injuries include the maturation stage of the traumatic teeth, mobility, direction of displacement, distance of displacement, and whether there are alveolar fractures. In avulsion, the maturation stage of the permanent tooth, the out-socket time, storage media/condition of the avulsed tooth, and management of the PDL should also be considered. Especially, in this review, we have subdivided the immature tooth into the adolescent tooth (Nolla stage 9) and the very young tooth (Nolla stage 8 and below). This consensus paper aimed to discuss the impacts of those factors on the trauma management and prognosis of TDI to provide a streamlined guide for clinicians from clinical evaluation, diagnostic process, management plan decision, follow-up, and orthodontic treatment for tooth luxation and avulsion injuries.